Prilep, North Macedonia. House taskscapes in the Early Neolithic of the Pelagonia Valley: micro-refuse analyses. First results of the Campaign 2019 - Antolín, Ferran; Dimitrijević , Vesna; Naumov, Goce; Sabanov, Amalia; Soteras, Raül (e-Forschungsberichte des DAI, 2021)
New research, which involves the systematic collection of sediment samples, their treatment with the wash-over method, extraction of micro-refuse, and their subsequent analysis, started being implemented at archaeological sites in the Pelagonia Valley (North Macedonia) in the summer of 2019. Three Early Neolithic (ca. 6000–5800 cal BC) sites are being investigated and compared, with a focus on archaeobotanical materials, but also on other environmental and palaeoeconomic evidence. This paper presents the methodology applied and the first results from a series of samples (those for which the analyses were completed in 2021) from the 2019 campaign at the site of Vrbjanska Čuka. The goal is to illustrate the potential of micro-refuse analysis of samples coming from house contexts.